Coke Strength And Tuyere Velocity - Morimasa Ichida (The Minerals, Metals and Materials Society, 2006)
One of the key factors of stabilized blast furnace operation under the conditions of high productivity and high pulverized coal rate is to enlarge the raceway to reduce the dead man area. With a reduced dead man area, the descent area is enlarged and the central gas flow is maintained at the same time. In this study, raceway furnace experiments were conducted with tuyere velocity and coke strength changed both in hot and cold conditions to measure the coke degradation rate. Using the coke degradation rate measurements, we examined the equivalent relation between the coke strength and tuyere velocity for coke degradation in the raceway. In addition, in this paper, we discuss the increase in tuyere velocity in relation to an increase in coke strength.